Propriedades estruturais, elétricas e ópticas do composto LaCrO3 dopado com Al produzido pelo método da combustão - Silva Junior, Romualdo Santos (2018)
In the present work, we performed a study of the structural, electrical and optical properties of the compound LaCr1-xAlxO3 (x = 0.0, 0.05, 0.5, 0.95 and 1.0) produced by the combustion method. The structural analyzes were performed by X-ray diffraction (XRD) and Rietveld refinement, the electrical measurements using impedance spectroscopy and IV measurements, and optical measurements using UV-Vis spectroscopy. The results of XRD allied to the Rietveld method of refinement indicate that the samples with x = 0.0 and 0.05, have an orthorhombic structure belonging to the space group Pnma (62), and for x = 0.5, 0.95 and 1.0, a rhombohedral structure belonging to the space group R-3c (167), thus taking place a structural transition in the material. The impedance spectroscopy measurements associated to the IV curves show that the samples with higher concentration of Al present higher resistance, and the samples with lower concentration of Al present less resistance. We observe that for high frequencies a decrease of dielectric constant with frequency occurs. In addition, the appearance of only a semicircle establishes the presence of non-Debye type relaxation, where an equivalent circuit composed of two resistors (R1 and R2) and a constant phase element (CPE) were used. By means of the absorption measurements in the ultraviolet to visible region (UV-Vis), we estimated the optical gap of the samples, through the tauc equation, which vary between 3.27 - 3.43 eV. Still, we observed that the increase in Al concentration favors the increase in transmittance in the material.